New Trend in Narcotic Drugs Synthetic Cannabinoids - Artuç, Selahattin; Doğan, Kamil Hakan; Demirci, Şerafettin (The Bulletin of Legal Medicine, 2014)
Natural cannabis (Δ9-THC, tetrahydrocannabinol) is obtained from Indian hemp plant (Cannabis sativa) and it acts on cannabinoid receptors expressed as CB1, CB2. The therapeutic effects of cannabis is known from far away times. At the present time, some drugs containing kannabinoid are used for medical purposes. Synthetic cannabinoids’ chemical structure is quite different than natural cannabis. Cannabinoid receptor affinity and activity are greater than the natural cannabis. Substances containing synthetic cannabinoids are generally called “Spice”, “K2” abroad and, “Bonzai” or “Jamaica” in Turkey. Legal sale of herbal mixtures containing synthetic cannabinoids at places called “head shop” and “smart shop” in some countries and having easily access to them from the internet is an attractive feature for users. Moreover the impact stronger than cannabis, affordability, easy accessibility and getting rid of standard material tests contribute to increasing use of synthetic cannabinoids. As there is absence of reference standards of synthetic cannabinoids, it is not easy to identify them. In order to overcome legal barriers, new cannabinomimetic analogs are presented to market constantly. When taking into consideration of the increase of the use of synthetic cannabinoids, it is expected to be one of the most problematic drugs in the near future. Due to the widespread abuse of synthetic cannabinoids, further investigation of these substances is needed for better identification of their pharmacology and toxicology and to make appropriate legal planning and arrangements.Keywords: Synthetic cannabinoid, bonzai, narcotic drug.
Keywords: synthetic cannabinoid; bonsai; narcotic drug